Comparative study of analysis filter bank designs for AC-3 encoding - Tan, Mark Joseph L. (2007)
Several high-fidelity audio formats have been developed with the challenge of developing audio coding techniques intended for low cost, limited bandwidth and storage capacity. AC-3 is one of these international standards. It has been widely used as the audio coding standard for laserdiscs, cinemas and DVD films, AC-3 has been accepted by the Advanced Television Systems Committee (ATSC) as the audio coding standard for US Grand Alliance High Definition Television (HDTV) system. This project is a comparative study of analysis filter bank designs for AC-3 encoding. Optimization techniques on the analysis filter bank designs will be performed. Listening and speed performance tests will also be done to compare the optimized codes with the standard implementation. The project will aid in future designs concerning the AC-3 audio coding standard, with the goal of improving performance and efficiency for high-quality digital audio compression.
Thesis (B.S. Computer Engineering)--University of the Philippines Diliman.
Keywords: Sound -- Recording and reproducing -- Digital techniques -- Standards; Filter bank designs; AC3 encoder; Audio coding standard